(untitled) (African Journal of Law and Politics, 2025)
Contracts of carriage of goods by sea are, because they involve trans-border trade regulated by international conventions. Rather than inspire the harmony required to foster trade and ensure social harmony, these conventions are an epitome of cacophony. With the intention of protecting certain parties, the rights and obligations are lopsided and there is differential consideration in the formulation of certain important concepts. With a view to triggering a review of the conventions, this paper highlights and analyses some of the provisions. Of interest to this writer are the rights and obligations of the parties, the conception of the parties to a contract of carriage of goods by sea, inter alia, and notion of a contract of carriage of goods by sea.